2015
DOI: 10.7554/elife.08789
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of GABA and resting state functional connectivity by transcranial direct current stimulation

Abstract: We previously demonstrated that network level functional connectivity in the human brain could be related to levels of inhibition in a major network node at baseline (Stagg et al., 2014). In this study, we build upon this finding to directly investigate the effects of perturbing M1 GABA and resting state functional connectivity using transcranial direct current stimulation (tDCS), a neuromodulatory approach that has previously been demonstrated to modulate both metrics. FMRI data and GABA levels, as assessed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
192
5
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 203 publications
(223 citation statements)
references
References 34 publications
20
192
5
1
Order By: Relevance
“…Antonenko et al [29] reported a reduction of GABA concentrations following atDCS together with a decreased FC in the sensorimotor cortex in elderly. This pattern is different from that observed in young adults [30, 31, 39]. Stratification of the elderly sample into younger (< 63 age) and older (> 63 age) revealed a differential effect of atDCS-induced GABA modulation and network coupling: in younger, lower GABA correlated with higher sensorimotor strength (i.e., the same pattern observed in young adults), while in older the correlation was reversed [29].…”
Section: Mechanisms Of Network Modulation: Brain Neurometabolitesmentioning
confidence: 79%
See 3 more Smart Citations
“…Antonenko et al [29] reported a reduction of GABA concentrations following atDCS together with a decreased FC in the sensorimotor cortex in elderly. This pattern is different from that observed in young adults [30, 31, 39]. Stratification of the elderly sample into younger (< 63 age) and older (> 63 age) revealed a differential effect of atDCS-induced GABA modulation and network coupling: in younger, lower GABA correlated with higher sensorimotor strength (i.e., the same pattern observed in young adults), while in older the correlation was reversed [29].…”
Section: Mechanisms Of Network Modulation: Brain Neurometabolitesmentioning
confidence: 79%
“…The majority of these studies investigated neurometabolite changes in the motor cortex in young adults, reporting a consistent reduction of GABA after atDCS [31, 70, 75, 76], except for Tremblay et al [77]. The above finding was generally coupled with increased FC over the motor network [31, 39], indicating that these connectivity changes may be driven by a decrease in the inhibitory neurotransmitter.…”
Section: Mechanisms Of Network Modulation: Brain Neurometabolitesmentioning
confidence: 86%
See 2 more Smart Citations
“…During tDCS, however, the equipment was restored; the subject table was pulled out of the scanner while the participant lay supine and electrodes were reconnected to the tDCS device. Active tDCS was delivered for 20 min at 1 mA intensity with ramp-up/ramp-down periods of 10 sec, as described in earlier studies (Bachtiar et al, 2015;Stagg et al, 2013). For sham, the stimulator provides stimulation at the beginning and at the end to mimic the somatosensory artifact of active tDCS.…”
Section: Methodsmentioning
confidence: 99%